The Tom and Nan Riley Collection of Roman Portrait Sculptures - Cedar Rapids Museum of Art (2009)
[Dt.:] Präsentation von hellenistischen Porträts, Kaiserporträts und römischen Bildnissen von Privatleuten aus einer Sammlung, die dem Cedar Rapids Museum of Art in Iowa gestiftet worden ist. - [Engl.:] Presentation of hellenistic portraits, imperial portraits and portraits of private persons from a collection, which has been donated to the Cedar Rapids Museum of Art in Iowa.